The Use of Myocardial Performance Index (Mpi) in Assessment of Heart Function - Saeed, Basil N.; Salim, F.; ALsaynee, M-; ALsaynee, M-; Sunbul, L.- (AL-Kindy College Medical Journal, 2009)
Background: Ejection fraction have been used frequently for assessment of the left ventricular function, but can be associated with errors in which myocardial performance index have been used as another parameter to measure the left ventricular function. Objective: selecting another echocardiography parameter for the assessment of myocardial in function instead of the ejection fraction. Methods: 160 patients referred to the echocardiogram unit from the period december 2007 to august 2008 requesting assessment of left ventricular function. After clinical examination, routine blood tests; chest x-ray and electrocardiographic recording have been completed. All patients informed to come for this unit after the first visit monthly for three successive months. For the purpose of comparison (30) thirty volunteers admitted to this study as control having same age range. The (160) patients were categorized into two groups. Group (A) includes (70) patients with ischemic heart disease with complications like pulmonary oedema, myocardial infarction, recent admission to coronary care unit because of recurrent severs chest pain. Group (B) includes (90) patients with ischemic heart disease without any of the above complications. Myocardial performance index is done by using the four chambers view and pulse wave and curser along the mitral inflow of the blood jet. Results: Assessment of left ventricular function by using the myocardial performance index in group A was more significant than using the ejection fraction in comparison to the control group (P value 0.02, 0.03 respectively) the same was found in group B in comparison to control group (P value 0.01; 0.05 respectively). Conclusion The myocardial performance index (MPI) in the control groups was 0.44-0.36 MS indicating that its range is very narrow in the control group, The (MPI) in the two groups of patients was high in comparisons with control group